PENGARUH INSERVIS TRAINING AND UPGRADING TERHADAP KINERJA GURU PENDIDIKAN AGAMA ISLAM (STUDI KASUS DI SMP NEGERI 5 SENTAJO RAYA) - Angga Kutiba Alhuda (Universitas Islam Kuantan Singingi, 2020)
Competency development is a formal activity, including Islamic Religious Education teachers must be qualified and professional, because the objectives of Islamic religious education as mandated by the government can be achieved properly. The quality of teachers needed in this era is a teacher who is able and ready to play a role in a large environment, namely schools and communities. Problems in this study The Effect of Inservis Training and Upgrading on Teacher Performance of Islamic Religious Education and the factors that influence it in SMP Negeri 5 Sentajo Raya . Based on preliminary observations that the author carried out, seen several symptoms including: Teachers of Islamic Education have tried to improve their quality through various training but the results of field practice have not been maximized. Teachers have not planned learning well, have not carried out a quality learning process, and have not yet assessed and evaluated authentic learning outcomes. Teachers have not been able to continuously improve and develop academic qualifications and competencies in line with the development of science, technology, and art. Teachers still arrive late and go home prematurely. Training through MGMP has not been accompanied by coaching and improving the quality of knowledge and professionalism of teachers and PAI teachers have not been able to implement strategies, methods or techniques of learning that are interesting and fun for their students As the subjects in this study were 1 PAI teacher while as an object was the influence of Inservis Training and Upgrading on the performance of Islamic Religious Education teachers in SMP Negeri 5 Sentajo Raya, Sentajo Raya District Based on the results of data collection by observation, questionnaire, interview and documentation, the data were analyzed using the product moment formula Spearman rho statistical test it can be concluded that: The Effect of Training and Upgrading Inservis on the performance of Islamic Religious Education teachers in SMP Negeri 5 Sentajo Raya is 54 , 76%. Where the more often do the Inservis Training and Upgrading automatically the teacher's performance will get better too. Factors influencing the performance of Islamic Religious Education teachers as the results of the interview are: rarely have the opportunity to participate in various training. Less professional in implementing the 2013 curriculum and there is still much to be learned. There has been no visit or comparative study at other schools. Still have limited learning facilities and infrastructure such as insufficient infocus and projector facilities to support the learning process and there are still lack of experts in efforts to provide guidance in the 2013 curriculum in MGMP activities.